The Relationship between Confidence and Motivation with Learning Outcomes of Gymnastics Floor for Grade X MIPA Students in Kesamben Public High School - Novita Nur Synthiawati; Fitri Febriana Putri (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This study aims to determine the relationship of confidence with learning outcomes, motivation and learning outcomes of gymnastics on the floor. The research method used is the correlational research method. Sampling in this study using a cluster random sampling method, as many as 105 respondents. Data collection techniques using a questionnaire (questionnaire). Scoring instruments are based on a Likert scale. Data analysis includes regression analysis tests (simple and multiple), F test and correlation test. The results of this study: (1) the test results of the regression coefficient of confidence (X1) are related to the learning results of the floor gymnastics (Y), evidenced from the Ftable of 3.09 while the Fcount of 404,853, thus the value of Fcount> Ftable or 404,854> 3.09 with sig 0,000 <ɑ (0,05) it can be concluded that self-confidence is related to learning outcomes of the floor exercise. (2) the results of the motivation regression coefficient test (X2) are related to the learning outcomes of floor gymnastics (Y), as evidenced by the Ftable of 3.09 while the Fcount of 65.687, thus the value of Fcount> Ftable or 65.687> 3.09 with sig 0.000 <ɑ (0.05) it can be concluded that motivation is related to learning outcomes of floor exercises. So there is a relationship between self-confidence and motivation with the results of learning to exercise floor. Suggestions for paying attention to factors other than self-confidence and motivation that play a role or are related to learning outcomes of gymnastics on the floor.